[tex]a)\\\\\sqrt{16*9}=\sqrt{16}*\sqrt{9}=4*3=12\\\\b)\\\\\sqrt{100*64}=\sqrt{100}*\sqrt{64}=10*8=80\\\\c)\\\\\sqrt{ 6^2*5^2}=\sqrt{ 6^2}*\sqrt{5^2} =6*5=30\\\\d)\\\\\sqrt{4*81*9}=\sqrt{4}*\sqrt{81}*\sqrt{9}=2*9*3=54[/tex]
[tex]f)\\\\\sqrt{11^2*2^2*3^4}=\sqrt{11^2}*\sqrt{2^2}*\sqrt{(3^2)^2}=11*2*3^2=22*9=198\\\\g)\\\\\sqrt[3]{27*64}=\sqrt[3]{27}*\sqrt[3]{64}=3*4=12\\\\h)\\\\\sqrt[3]{8*64}=\sqrt[3]{8}*\sqrt[3]{64}=2*4=8\\\\i)\\\\\sqrt[3]{7^3*9^3}=\sqrt[3]{ 7^3}*\sqrt[3]{9^3}=7*3=21[/tex]
[tex]j)\\\\\sqrt[3]{27*64*125}=\sqrt[3]{ 27}*\sqrt[3]{64}*\sqrt[3]{125}= 3*4*5=60\\\\k)\\\\\sqrt[3]{ 3^6*5^3*2^9}=\sqrt[3]{ 3^6}*\sqrt[3]{ 5^3}*\sqrt[3]{ 2^9}=\sqrt[3]{(3^2)^3}*5*\sqrt[3]{(2^3)^3}=3^2*5*2^3=9*5*8=360\\\\l)\\\\\sqrt[3]{ 4^9*6^3*27}=\sqrt[3]{ 4^9}*\sqrt[3]{ 6^3}*\sqrt[3]{ 3^3}=\sqrt[3]{ (4^3)^3}*\sqrt[3]{ (6^2)^3} *3= 4^3*6^2*3=64*36*3= 6912[/tex]